The evaluation of an Online peer support group on the levels of internal and external self-confidence among undergraduate students during Covid-19 pandemic: a Bandura’s Theory of Self-Efficacy Approach - Kamal Ariffin, Nurul Afiqah; Waisulqrnai, Siti Adibah; Ahmad Fisal, Nur Sakinah Habibah; Syed Lohikmal Hakim, Sharifah Amirah Fikriyyah; Azman, Intan Nur Athirah; Safarazi, Siti Nur Fatehah; Sharif, Shafiqah Nadhrah; Abdul Penyu, Mohd Izzati Rezuan; Lourdunathan, Pamilia (IIUM Press, International Islamic University Malaysia, 2022)
The Covid-19 pandemic had a great impact on individuals of all walks of life in the aspect of psychosocial functioning particularly those from a B40 background as well as students. The main objective of this study was to evaluate the effectiveness of a psycho socio-spiritual educational support group using the Bandura’s Theory of Self-Efficacy approach on the levels of internal and external self-confidence among 4th-year undergraduate IIUM students during the Covid-19 pandemic. It also aims to identify the issues of self-confidence from the participants during Covid-19. Seven 4th-year IIUM undergraduate students have been interviewed to identify the self-confidence issues and 22 participants (N=22) from the age of 22 to 24 years old were recruited via purposive sampling method to participate in the online peer support group. The present study used a mixed-method, exploratory approach with a quasi-experimental one-group pre-test-post-test design and a qualitative design. Two questionnaires have been utilized, the internal and external self-confidence scale by Kelsey Evelyn Perkins, and in-depth interviews employed five open-ended questions. The Likert scales consisted of 12-items that required participants to rate from 1“strongly disagree to 7 “strongly agree.” Data were analysed qualitatively by thematic analysis and quantitatively using Paired Sample T-test computed in the 26.0 version of Statistical Package for the Social Sciences (SPSS) with a P-value <0.5 considered statistically significant. There was a statistically significant increase in Internal Self Confidence pre-test score (M=55.64, SD=9.459) to Post-test (M=69.55, SD=9.012), t(21)=5.670, p<0.05 (two-tailed). There was also an increment for External Self Confidence pre-test score, (M= 41.00, SD=10.156) and post-test (M=50.18, SD=13.800), t(21)=3.217, p<0.05 (two-tailed) after the implementation of the online peer support group among undergraduate students during the Covid-19 pandemic. According to the current research, peer support might be a helpful tool to improve self-confidence among undergraduate students and broaden its function as a coping mechanism to improve the quality of life and well-being. The findings of this research will also shed light on the use of Bandura’s Theory of Self-Efficacy in the fostering of Internal and External Self-confidence.